Application of TMPRSS12 gene in preparation of medicine for preventing or treating novel coronavirus infection - ZHANG CHUN; JIANG LI; DING NING; LIU JIANFENG (2023)
The invention relates to the field of biological medicine. Specifically, the invention relates to application of TMPRSS12 protein or an inhibitor thereof in preparation of a medicine for preventing and/or treating diseases and/or symptoms caused by SARS-CoV-2 infection of a subject. The invention also relates to a method for screening a medicine for preventing and/or treating diseases and/or symptoms caused by SARS-CoV-2 infection. Therefore, the TMPRSS12 protein or the inhibitor of the TMPRSS12 protein has great potential in prevention, treatment and targeted drug screening of the novel coronavirus. 本申请涉及生物医药领域。具体来说，本申请涉及TMPRSS12蛋白或其抑制剂在制备预防和/或治疗受试者的由SARS-CoV-2感染导致的疾病和/或症状的药物中的用途。本申请还涉及一种筛选用于预防和/或治疗SARS-CoV-2感染导致的疾病和/或症状的药物的方法。因此，本申请的TMPRSS12蛋白或其抑制剂在新型冠状病毒的预防、治疗以及靶向药物筛选中具有较大的潜能。